Does Time for (in)Direct Nursing Care Activities at the End of Life for Patients With or Without Specialized Palliative Care in a University Hospital Differ? A Retrospective Analysis. (October 2020) - Fliedner, Monica C.; Hagemann, Monika; Eychmüller, Steffen; King, Cynthia; Lohrmann, Christa; Halfens, Ruud J. G.; Schols, Jos M. G. A.
Background: Nurses' end of life (EoL) care focuses on direct (eg, physical) and indirect (e, g, coordination) care. Little is known about how much time nurses actually devote to these activities and if activities change due to support by specialized palliative care (SPC) in hospitalized patients. Aims: (1) Comparing care time for EoL patients receiving SPC to usual palliative care (UPC);(2) Comparing time spent for direct/indirect care in the SPC group before and after SPC. Methods: Retrospective observational study; nursing care time for EoL patients based on tacs® data using nonparametric and parametric tests. The Swiss data method tacs measures (in)direct nursing care time for monitoring and cost analyses. Results: Analysis of tacs® data (UPC, n = 642; SPC, n = 104) during hospitalization before death in 2015. Overall, SPC patients had higher tacs® than UPC patients by 40 direct (95% confidence interval [CI]: 5.7-75, P = .023) and 14 indirect tacs® (95% CI: 6.0-23, P < .001). No difference for tacs® by day, as SPC patients were treated for a longer time (mean number of days 7.2 vs 16, P < .001).Subanalysis for SPC patients showed increased direct care time on the day of and after SPC ( P < .001), whereas indirect care time increased only on the day of SPC. Conclusions: This study gives insight into nurses' time for (in)direct care activities with/without SPC before death. The higher (in)direct nursing care time in SPC patients compared to UPC may reflect higher complexity. Consensus-based measurements to monitor nurses' care activities may be helpful for benchmarking or reimbursement analysis.